Search for trilepton signatures from associated gaugino pair production - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; Astur, R; et al. (1998)
We report on a search for the trilepton decay signature from the associated production of supersymmetric gaugino pairs, χ̃1±χ̃20, within the context of minimal supersymmetric models that conserve R parity. This search uses 95 pb-1 of pp̄ data taken at √s = 1.8 TeV with the D0 detector. No evidence of a trilepton signature has been found, and a limit on the product of cross section times branching fraction to trileptons is given as a function of χ̃1± mass.